Challenging perspectives on mathematics classroom communication - Chronaki, Anna; Christiansen, Iben Maj (International perspectives on mathematics education, 2004)
The editors and contributors of these ten articles focus on the idea that communication includes both what is happening and being said among participants in a classroom and also the politics, values and ideologies that serve as the foundation of the practice. They describe how communication thereby involves register, representation and contexts through media-human interfaces in the classroom and in interpreting mathematics as a text, how communication in mathematics teaching becomes social interaction in cooperative settings and classroom activities, and how communication translates into practice, community, identity and policy.